Advancements in autologous peripheral nerve transplantation care: a review of strategies and practices to facilitate recovery - Xu, Guoying; Zou, Xiaodi; Dong, Yanzhao; Alhaskawi, Ahmad; Zhou, Haiying; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Alenikova, Olga; Abdalbary, Sahar Ahmed; Lu, Hui (Frontiers in Neurology, 2024)
Autologous peripheral nerve transplantation, a pioneering technique in nerve injury treatment, has demonstrated remarkable progress. We examine recent nursing strategies and methodologies tailored to various anatomical sites, highlighting their role in postoperative recovery enhancement. Encompassing brachial plexus, upper limb, and lower limb nerve transplantation care, this discussion underscores the importance of personalized rehabilitation plans, interdisciplinary collaboration, and innovative approaches like nerve electrical stimulation and nerve growth factor therapy. Moreover, the exploration extends to effective complication management and prevention strategies, encompassing infection control and pain management. Ultimately, the review concludes by emphasizing the advances achieved in autologous peripheral nerve transplantation care, showcasing the potential to optimize postoperative recovery through tailored and advanced practices.